Characterization of the novel OXA-213-like β-lactamase OXA-822 from Acinetobacter calcoaceticus. (17th November 2020) - Tietgen, Manuela; Leukert, Laura; Sommer, Julian; Kramer, Jan S; Brunst, Steffen; Wittig, Ilka; Proschak, Ewgenij; Göttig, Stephan
Abstract: Objectives: This study analysed the novel carbapenem-hydrolysing class D β-lactamase OXA-822 identified in the clinical Acinetobacter calcoaceticus isolate AC_2117. Methods: WGS was employed for identification of β-lactamases. Micro-broth dilution was used for evaluation of antibiotic susceptibility of AC_2117 and transformants containing bla OXA-822 . After heterologous purification of OXA-822, OXA-359 and OXA-213, enzyme kinetics were determined using spectrometry. The effect of OXA-822 upon meropenem treatment was analysed in the Galleria mellonella in vivo infection model. Results: OXA-822 is a member of the intrinsic OXA-213-like family found in A. calcoaceticus and Acinetobacter pittii. Amino acid sequence similarity to the nearest related OXA-359 was 97%. Production of OXA-822, OXA-359 and OXA-213 in Acinetobacter baumannii ATCC ® 19606 T resulted in elevated MICs for carbapenems (up to 16-fold). Penicillinase activity of the purified OXA-822 revealed high KM values, in the millimolar range, combined with high turnover numbers. OXA-822 showed the highest affinity to carbapenems, but affinity to imipenem was ∼10-fold lower compared with other carbapenems. Molecular modelling revealed that imipenem does not interact with a negatively charged side chain of OXA-822, as doripenem does, leading to the lower affinity. Presence of OXA-822 decreased survival of infected Galleria mellonella larvae after treatment with meropenem. Only 52.7% ± 7.7% of the larvae survived after 24 h compared with 90.9% ± 3.7% survival in the control group. Conclusions: The novel OXA-822 from a clinical A. calcoaceticus isolate displayed penicillinase and carbapenemase activity in vitro, elevated MICs in different species and decreased carbapenem susceptibility in A. baumannii in vivo .